Sport Tourism di Sabang: Transformasi Wisata Olahraga sebagai Instrumen Branding Kota - Ridha Aulia (Sociale : Journal of Social Science, 2026)
This study aims to understand how sport tourism in Sabang can transform into a sustainable city branding instrument, emphasizing the relationship between natural potential, socio-cultural traditions, and the creative economy of the local community. This study uses a qualitative approach with an interpretative paradigm, which allows researchers to explore the meanings, perceptions, and experiences of the actors involved. Data were collected through in-depth interviews with local government, tourism businesses, sports communities, and tourists, participant observation of sport tourism activities, and a review of tourism policy and promotion documents. Analysis was conducted thematically, emphasizing the processes of reduction, categorization, and interpretation to find relevant patterns of meaning. The results show that Sabang has great potential to develop sport tourism through its geographical advantages, marine ecology, and maritime traditions, but still faces challenges such as limited infrastructure, inconsistent international promotion, and threats to ecological sustainability. The discussion emphasizes that sport tourism can be an effective city branding instrument if developed with an integrative approach, involving synergy between the government, community, and business actors, and prioritizing environmental sustainability. Thus, sports tourism in Sabang is not only a tourist attraction but also a city branding strategy that can strengthen local identity, stimulate the creative economy, and increase global competitiveness.